Identification of the promoter of the myelomonocytic leukocyte integrin CD11b. - Hickstein, D D (1992)
The CD11b (or macrophage-1 antigen; MAC-1) subunit of the leukocyte integrin family forms a noncovalently associated heterodimeric structure with the CD18 (beta) subunit on the surface of human granulocytes and monocyte/macrophages, where it enables these myeloid cells to participate in a variety of adherence-related activities. Expression of the CD11b subunit is restricted to cells of the myelomonocytic lineage and depends upon the stage of differentiation with the most mature myeloid cells expressing the highest levels of CD11b. To study the regulation of CD11b expression, a genomic clone corresponding to the 5' region of the CD11b gene was isolated from a human chromosome 16 library. Primer extension and RNase protection assays identified two major transcriptional start sites, located 90 base pairs and 54 base pairs upstream from the initiation methionine. DNA sequence analysis of 1.7 kilobases of the 5' flanking sequence of the CD11b gene indicated the absence of a "CAAT" or "TATA" box; however, potential binding sites for the transcription activators Sp1, PU.1, ets, and AP-2 are present, as well as retinoic acid response elements. The 1.7-kilobase CD11b promoter sequence displayed functional activity in transient transfection assays in the monocytic cell line THP-1 and the myeloid cell line HL-60. In contrast, this 1.7-kilobase promoter sequence did not display functional activity in the Jurkat T-lymphoid cell line. Detailed characterization of the CD11b promoter sequence should provide insight into the molecular events regulating the tissue-specific and developmental stage-specific expression of the CD11b molecule in myelomonocytic cells.